DESAFIOS DO FINANCIAMENTO DAS UNIVERSIDADES ESTADUAIS PAULISTAS - Alberto Teixeira Protti; Carlos Antonio Luque; Hélio Nogueira da Cruz (Revista Gestão Universitária na América Latina, 2012)
This paper discusses the financing of State Universities of São Paulo in front of the increase of yearly enrollment in undergraduate courses and the growth of pressure on the Education System’s budget after the rise in the minimum percentage of investment in basic education approved by the Brazilian Congress. Since 1989 the State Universities of São Paulo have been treated as autonomous institutions and their budgets linked to ICMS, one of the most important taxes of state of São Paulo. However, this pattern of financing is fragile because it depends on the approval of state assembly, while the investment in basic education is defined by the Constitution. In the case of shortage of financial resources this fragility may become relevant and the Universities may have to deal with a budget reduction or find alternatives to their funding.